2019
DOI: 10.1101/573899
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A practical computerized decision support system for predicting the severity of Alzheimer’s disease of an individual

Abstract: 1Computerized clinical decision support systems can help to provide objective, standardized, 2 and timely dementia diagnosis. However, current computerized systems are mainly based 3 on the group analysis, discrete classification of disease stages, or expensive and not readily 4 accessible biomarkers, while current clinical practice relies relatively heavily on cognitive and 5 functional assessments (CFA). In this study, we developed a computational framework using 6 a suite of machine learning tools for ident… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 122 publications
3
27
0
Order By: Relevance
“…In a study using the Alzheimer's Disease Neuroimaging Initiative (ADNI) data for AD prediction, XGBoost demonstrated superior results (AUC = 0.97 (0.01) when including imaging parameters (MRI and PET) as predictors and when compared to RF, Support Vector Machines, Gaussian Processes and Stochastic Gradient Boosting [16]. In another study where cognition and MRI were used as predictors, Kernel Ridge Regression was performed to R 2 = 0.87 (0.025) when cognition and MRI predictors were included [17].…”
Section: Discussionmentioning
confidence: 99%
“…In a study using the Alzheimer's Disease Neuroimaging Initiative (ADNI) data for AD prediction, XGBoost demonstrated superior results (AUC = 0.97 (0.01) when including imaging parameters (MRI and PET) as predictors and when compared to RF, Support Vector Machines, Gaussian Processes and Stochastic Gradient Boosting [16]. In another study where cognition and MRI were used as predictors, Kernel Ridge Regression was performed to R 2 = 0.87 (0.025) when cognition and MRI predictors were included [17].…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work, we have shown that CFAs are among the most predictive features for classifying AD severity [40], [41]. For the current clinical dataset, the CFAs included Addenbrooke’s Cognitive Examination (ACE-III) and the Mini-ACE [42], the Bristol Activities of Daily Living Scale [43], the Geriatric Depression Scale [44], the NPI-Q behavioral, distress and severity measurements [45], and the Zarit Caregiver Burden [46].…”
Section: Methodsmentioning
confidence: 99%
“…CDRSB has a total score range from 0 to 18 points, with higher scores indicating greater cognitive impairment. CDRSB has been commonly used as a reliable tool for assessing dementia severity [27,28].…”
Section: Methodsmentioning
confidence: 99%